Consonant Enhancement Effects on Speech Recognition of Hearing-Impaired Children - Smith, Lynn Z.; Levitt, Harry (Journal of the American Academy of Audiology, 1999)
Differences in gain (enhancement, in dB) required to optimize the consonant/vowel intensity ratio in nonsense syllables were determined for stops and fricatives, both voiced and voiceless, in 12 children with congenital moderate to severe sensorineural hearing loss. The test stimuli were vowel/consonant nonsense syllables with various levels of enhancement ranging from 0 dB (for the unprocessed stimulus) to 24 dB of gain, in steps of 3 or 6 dB. Results showed that significant improvements in consonant recognition can be obtained with individualized adjustment of consonant amplitude for children as young as 5 years of age.Abbreviations: CE = consonant enhacement, CVR = consonant/vowel intensity ratio, NST = Nonsense Syllable Test
Keywords: Children; hearing impaired; speech perception